1997
DOI: 10.1103/physrevd.56.6895
|View full text |Cite
|
Sign up to set email alerts
|

Precision corrections to dispersive bounds on form factors

Abstract: We present precision corrections to dispersion relation bounds on form factors in bottom hadron semileptonic decays and analyze their effects on parameterizations derived from these bounds. We incorporate QCD two-loop and nonperturbative corrections to the two-point correlator, consider form factors whose contribution to decay rates is suppressed by lepton mass, and implement more realistic estimates of truncation errors associated with the parameterizations. We include higher resonances in the hadronic sum th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
411
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(437 citation statements)
references
References 57 publications
13
411
1
Order By: Relevance
“…, a N }, with the remaining infinite set bounded in magnitude and forming a theoretical truncation error [7], δ N : 4) which means that the form factor fit to these parameters using (2.5) has a theoretical uncertainty no larger than δ N . The kinematic parameter t s is used to minimize the size of this already small truncation error [1,5]. Equation (4.4) makes it clear that this minimization occurs when z = 0 lies within the kinematic range chosen for the fit, t ∈ [t min , t max ]; from (2.4) one sees that this can occur only if t s also assumes some value in this range.…”
Section: Parameterization and Quality Of Fitmentioning
confidence: 99%
See 2 more Smart Citations
“…, a N }, with the remaining infinite set bounded in magnitude and forming a theoretical truncation error [7], δ N : 4) which means that the form factor fit to these parameters using (2.5) has a theoretical uncertainty no larger than δ N . The kinematic parameter t s is used to minimize the size of this already small truncation error [1,5]. Equation (4.4) makes it clear that this minimization occurs when z = 0 lies within the kinematic range chosen for the fit, t ∈ [t min , t max ]; from (2.4) one sees that this can occur only if t s also assumes some value in this range.…”
Section: Parameterization and Quality Of Fitmentioning
confidence: 99%
“…Recently, attention has increased due to studies of bounds obtained on form factors from heavy hadron semileptonic decays, which can be used in concert with Heavy Quark Effective Theory to isolate the CKM elements |V cb | and |V ub | (see [1] for a compilation of references). Such studies were initially motivated by the 1981 paper of Bourrely, Machet, and de Rafael [2], which first applied the basic method of equating the dispersion integral over hadronic form factors to its perturbative QCD evaluation in the deep Euclidean region, in that paper for the case of K ℓ3 decays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment, the most precise determinations of |V cb | from inclusive [6,7] and exclusive decays [8] differ from each other at ≈ 3σ confidence level (CL). Recently it has been shown that the CapriniLellouch-Neubert (CLN) [9] and Boyd-Grinstein-Lebed (BGL) [10] parameterizations lead to different results for the exclusive determinations of |V cb | [11,12]. In their analysis they have used up-to-date lattice calculations of the form factors along with the available experimental results from Belle [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the slope and the curvature, the lower bounds (29) and (33) are complementary to the upper bounds obtained from unitarity constraints [10], [11].…”
mentioning
confidence: 99%